MAKING PLAY WITH TURBO PASCAL OTHELLO - Sugiyanto Sugiyanto; Don Elsyafitri, SKom (Jurnal Sistem Informasi, 1999)
Input with a mean 4.6 mengtikan eg the fourth row and column that we declare toenam.Lalu jum_cek = 0, then run a procedure cek_atas, here to be tested whether thetype of disc that is input or at the range that we fill, empty or still the same color(Does not contain a disc) with a disc that was on it, if you have then read the nextprocedure.